The Effectiveness Of Messages At Press Meetings In Delivery Of Activities Of The Bengkulu Province Of The Regional Governmen (Study at Media Center Diskominfo Bengkulu Province) - Febi Andriyani; Asnawati Asnawati; Sapta Sari (Penerbit Jurnal Indonesia, 2022)
This study aims to describe the effectiveness of Media Center communication at the Bengkulu Province Diskominfo about Bengkulu Free from Corona Virus. The research method used is qualitative research and data collection techniques through observation, interviews and documentation. In this analysis method, the Wilbur Scram approach is used in the message component. The results show that the effectiveness of the message conveyed by the Bengkulu Province Diskominfo through the Bengkulu Governor Rohidin Mersyah contains about the corona virus, namely the message must be designed, the message must be directed to the address, the message must be according to personal needs and the message must suggest a proper need.